2013
DOI: 10.1002/jgra.50174
|View full text |Cite
|
Sign up to set email alerts
|

Can a nightside geomagnetic Delta H observed at the equator manifest a penetration electric field?

Abstract: [1] A prompt penetration electric field (PPEF) usually manifests itself in the form of an equatorial ionospheric electric field being in correlation with a solar wind electric field. Due to the strong Cowling conductivity, a PPEF on the dayside can be inferred from Delta H (ΔH), which is the difference in the magnitudes of the horizontal (H) component between a magnetometer at the magnetic equator and one off the equator. This paper aims to investigate the performance of ΔH in response to a PPEF on the nightsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…From Figure it can be said that a westward (convection) electric field has penetrated for about 6 hr at least in the nightside ionosphere. The nightside EEJ was an order of magnitude smaller than the dayside EEJ as shown for geomagnetic storms (Tsuji et al, ; Wei et al, ) and substorms (Hashimoto et al, ), which indicates penetration of the electric field to the nightside equatorial ionosphere.…”
Section: Resultsmentioning
confidence: 75%
“…From Figure it can be said that a westward (convection) electric field has penetrated for about 6 hr at least in the nightside ionosphere. The nightside EEJ was an order of magnitude smaller than the dayside EEJ as shown for geomagnetic storms (Tsuji et al, ; Wei et al, ) and substorms (Hashimoto et al, ), which indicates penetration of the electric field to the nightside equatorial ionosphere.…”
Section: Resultsmentioning
confidence: 75%
“…However, several researchers reported PPEF signatures in ΔH on the nightside (Fejer et al, 2007;Galav et al, 2011). Moreover, Wei et al (2013) concluded that nightside ΔH can sometimes manifest a PPEF in the midnight-dawn sector (00-05 LT). We observed that on 28 May, ΔH increased between 2-8 UT (23-5 LT), this may be associated with an eastward penetration electric eld.…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent papers reported discernable PPEF signatures in DH on the nightside, where the Cowling conductivity is very weak [25,26]. Based on a multiple penetration event, Wei et al [27] suggested that the nightside DH was caused by the attenuation of the effects of polar electric field with decreasing latitude; the nightside DH can manifest PPEF at least in the midnight-dawn sector, but not always.…”
Section: The Patterns Of Ppefmentioning
confidence: 99%